Creation and valuation of instruments compensating lower share prices with the help of black-scholes formula - Leszek Zaremba (Foundations of Management, 2017)
In this paper, we present a 1-period model of the Polish financial market from the view point of KGHM, the Polish largest listed company that suffered huge declines in share prices from 125 PLN in August 2015 to 60 PLN in January 2015. Our goal is to show how KGHM might create a portfolio (with practically zero cost), which would fully compensate the abovementioned declines. The methodology presented below may be equally well employed by many other listed companies and investment funds, as well. We create here a matrix model of the Polish financial market and employ the Black-Scholes formula to valuate portfolios compensating potential declines of KGHM's shares prices. To give more insight to practitioners wishing to apply the results presented here to other listed companies, we distinguish two cases. In one of them, volatility of KGHM's share prices is 20%, and in the other case it equals 33%.
Keywords: 650; approximate hedging; Black Scholes formula; hedging; incomplete market; replication error; share prices